Hepatocellular carcinoma after a sustained virological response by direct‐acting antivirals harbors TP53 inactivation - Taisuke Imamura; Yukiyasu Okamura; Keiichi Ohshima; Katsuhiko Uesaka; Teiichi Sugiura; Takaaki Ito; Yusuke Yamamoto; Ryo Ashida; Katsuhisa Ohgi; Shimpei Otsuka; Sumiko Ohnami; Takeshi Nagashima; et al. (Cancer Medicine, 2022)
Abstract Introduction The genomic characteristics of hepatocellular carcinoma (HCC) after a sustained virological response (SVR) and its differences according to whether an SVR was achieved by treatment with direct‐acting antivirals (DAA) or interferon (IFN) are still not fully understood. Methods Sixty‐nine surgically resected HCCs from patients with hepatitis C virus infection were analyzed by gene expression profiling and whole‐exome sequencing. Results Among the 69 HCC patients, 34 HCCs in which an SVR was not achieved at the time of surgery were classified as HCV‐positive, and 35 HCCs in which an SVR was achieved at the time of surgery were classified as HCV‐SVR. According to the HCV treatment, 35 HCV‐SVR HCCs were classified into two groups: eight tumors with DAA (HCV‐SVR‐DAA) and 24 tumors with interferon (HCV‐SVR‐IFN). The frequency of samples with ARID2 mutations was significantly lower in HCV‐SVR than in HCV‐positive tumors (p = 0.048). In contrast, the frequency of samples with PREX2 mutations was significantly higher in HCV‐SVR samples than in HCV‐positive samples (p = 0.048). Among the patients with HCV‐SVR, the frequency of samples with TP53 mutations was significantly higher in HCV‐SVR‐DAA tumors than in HCV‐SVR‐IFN tumors (p = 0.030). TP53 inactivation scores in HCV‐SVR‐DAA tumors were found to be significantly enhanced in comparison to HCV‐SVR‐IFN tumors (p = 0.022). In addition, chromosomal instability and PI3K/AKT/mTOR pathway signatures were enhanced in HCV‐SVR‐DAA tumors. HCV‐SVR‐DAA was significantly associated with portal vein invasion (p = 0.003) in comparison to HCV‐SVR‐IFN. Conclusion Our dataset potentially serves as a fundamental resource for the genomic characteristics of HCV‐SVR‐DAA tumors. Our comprehensive genetic profiling by WES revealed significant differences in the mutation rate of several driver genes between HCV‐positive tumors and HCV‐SVR tumors. Furthermore, it was revealed that the frequency of samples with mutations in TP53 was significantly higher in HCV‐SVR‐DAA tumors than in HCV‐SVR‐IFN tumors.